2012
DOI: 10.1002/alr.21131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anatomical abnormalities in patients with limited and diffuse chronic rhinosinusitis

Abstract: These results suggest that patients with limited CRS may be predisposed by anatomical variants impairing drainage of the ostiomeatal region, and pansinusitis (likely resulting from generalized mucosal abnormality) is associated with a lower frequency of anatomical variants similar to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 9 publications
0
37
0
3
Order By: Relevance
“…Patients with RARS tend not to be treated surgically, and when they are, they undergo less extensive surgery than CRS patients. 16,17 Postoperatively they require fewer long-term medications. This…”
Section: Iiic Rs Definitions: Recurrent Acute Rhinosinusitismentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with RARS tend not to be treated surgically, and when they are, they undergo less extensive surgery than CRS patients. 16,17 Postoperatively they require fewer long-term medications. This…”
Section: Iiic Rs Definitions: Recurrent Acute Rhinosinusitismentioning
confidence: 99%
“…95 A 97-patient case-control study by Jain et al 16 examined patients with clinical symptoms of CRS and either CT evidence of pansinusitis or isolated maxillary/ostiomeatal complex (OMC) disease (classified as "limited sinusitis"). Both groups were compared to normal controls.…”
Section: Vb Ars: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that patients with RCMs had a higher Lund-Mackay radiological score for chronic rhinosinusitis than patients without cysts (2,12). It is generally believed that OMCO, accessory ostia, AMT, and NSD can lead to complaints or symptoms via chronic paranasal sinus inflammation (13)(14)(15)(16). Therefore, recurrent mucosal inflammation is a putative risk factor for the development of RCMs.…”
Section: Discussionmentioning
confidence: 99%